2001
DOI: 10.1053/rapm.2001.23931
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine added to the local anesthetic for brachial plexus block to provide postoperative analgesia in outpatients

Abstract: The addition of buprenorphine to the local anesthetic used for brachial plexus block in the present study provided a 3-fold increase in the duration of postoperative analgesia, with complete analgesia persisting 30 hours beyond the duration provided by the local anesthetic alone in 75% of the patients. This practice can be of particular benefit to patients undergoing ambulatory upper extremity surgery by providing prolonged analgesia after discharge from the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 18 publications
3
35
0
1
Order By: Relevance
“…12 et al and Bazin et al had observed a similar duration of analgesia (Median 20 hrs) on buprenorphine administration. In a similar way Candido et al (13) has observed duration of analgesia produced with buprenorphine 3 times longer than that produced by local anaesthetics alone. Wajima et al (14) has also found satisfactory and prolonged analgesia with butorphanol administered as continuous intrabrachial infusion.…”
Section: Discussionsupporting
confidence: 56%
“…12 et al and Bazin et al had observed a similar duration of analgesia (Median 20 hrs) on buprenorphine administration. In a similar way Candido et al (13) has observed duration of analgesia produced with buprenorphine 3 times longer than that produced by local anaesthetics alone. Wajima et al (14) has also found satisfactory and prolonged analgesia with butorphanol administered as continuous intrabrachial infusion.…”
Section: Discussionsupporting
confidence: 56%
“…Over the past ten years several studies have suggested that addition of certain opiates to the local anesthetic used for block anesthesia may provide effective and prolonged post-operative analgesia [7][8][9][10]. The presence of opioid receptors in peripheral nervous system offers the possibility of providing postoperative analgesia in ambulatory surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of opioid receptors in peripheral nervous system offers the possibility of providing postoperative analgesia in ambulatory surgical patients. Over the past decades many investigators have studied this approach and have compared the efficacy of various opioids added to the local anesthetics injected into inflamed dental tissues [4][5][6] and also in brachial plexus blocks [7][8][9][10]. Most of the studies pertaining to use of opioids mixed with local anesthetics were performed using 0.5 % bupivacaine which has longer duration of action.…”
Section: Introductionmentioning
confidence: 99%
“…The second useful adjuvant is clonidine which also prolongs the duration of most types of peripheral nerve block [37][38][39][40][41][42][43] The presence and clinical significance of peripheral opioid receptors that may be migratory and activated by inflammatory states, is widely debated. Candido et al [44,45] showed that buprenorphine added to a local anesthetic mixture (mepivacaine 1%, tetracaine 0.2% and epinephrine 1:200,000) significantly prolonged analgesia in both axillary and subclavian perivascular brachial plexus blocks, by up to 30 hours.…”
Section: Local Anesthetics and Additivesmentioning
confidence: 99%